“Investigating the Influence of Financial Literacy on Savings Behaviour Within College Students of Ernakulam District” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In today’s fast-paced world, young individuals often engage in excessive spending without fully understanding their financial limits. Financial literacy has become a crucial subject, particularly for the Gen Z population, as it directly impacts their financial decision-making. This research examines the level of financial literacy among college students in the Ernakulam district and its influence on their savings behavior. Financial literacy is assessed through three key components: financial knowledge, financial attitude, and financial management skills. The study explores how these independent variables collectively affect savings behavior, which serves as the dependent variable. Data was collected from 161 college students using a structured questionnaire distributed via Google Forms, and the results were analyzed using the Statistical Package for Social Sciences (SPSS). The findings highlight the significance of financial literacy programs in equipping young adults with essential financial skills, ultimately fostering better financial habits for their future.